INTEGRATING MATARAMAN CULTURE INTO ISLAMIC MANNER EDUCATION IN MI MA'ARIF PLAMPANG KULONPROGO SPECIAL PROVINCE OF YOGYAKARTA - Sukiyat Sukiyat; Abdul Munip (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2018)
Regulation of Kulon Progo Regent number 65 of 2017 concerning strengthening character education confirms that Mataraman culture must be part of the learning program at the elementary school, including the Madrasah Ibtidaiyah as an Islamic-based education. This article aims to describe how the integration of Mataraman culture in Islamic manners education at MI Ma'arif Plampang Kulon Progo in the implementation of classroom learning and its application in madrasas, using a differentiated integrative learning model. This research is qualitative. MI Ma'arif Plampang integrates the Mataraman culture and Islamic manners education based on the guidelines for strengthening character education regulated by the Regent of Kulon Progo, by emphasizing mutual respect according to the morals taught in the Islamic religion. The teaching material of Mataraman culture that is integrated into Islamic manners education is unggah-ungguh basa of Javanese language and literature with subjects of akidah-akhlak (Islamic creeds and morality). The developed values are religious values, courtesy, respect and obedience to others. Supporting factors include government policies regarding the use of traditional Javanese clothing in the style of Yogyakarta every Thursday Pahing, the quality of teachers and facilities for madrasa infrastructure, although there are inhibiting factors, namely inconsistent behavior from teachers and outsiders to the mixed culture.